Cervical cancer – does the morphological subtype affect survival rates?. (19th May 2018) - Emmett, Marta; Gildea, Carolynn; Nordin, Andrew; Hirschowitz, Lynn; Poole, Jason
Abstract: A retrospective population-based observational study using cancer registration data of women diagnosed with invasive cervical cancer between 2006 and 2010, in England, was carried out to explore how different morphological subtypes affect survival rates. Age-standardised net survival rates by morphological subtype are presented alongside with excess mortality modelling accounting for the impact of demographic, diagnostic and tumour factors. The three main morphological subtypes (squamous cell carcinoma (SCC), adenocarcinoma and adenosquamous carcinoma) have similar one-year net survival rates of approximately 85%. After adjusting for other important determinants of survival, there were no differences at five-years amongst the three main morphological subtypes, with unadjusted survival rates of 55–65%. As expected, women presenting with neuroendocrine tumours had a much poorer outcome than other epithelial cervical malignancies, with 1-year survival of up to 55%, five-year survival of 34% and excess mortality rates compared to SCC varying between 1.9 and 5.9. Impact Statement: What is already known on this subject: This is the first study on survival by cervical cancer morphological subtype using national cancer data. What the results of this study add: This study uses excess mortality modelling to investigate the effects of the morphological subtypes whilst adjusting the other factors that affect cervical cancer survival such as stage, age and grade. What the implications are of these findings for clinical practice and/or further research: It is known that cervical neuroendocrine tumours have a poor prognosis and this is confirmed by this study. Squamous cell carcinomas (SCC), adenocarcinomas (AC) and adenosquamous carcinomas (ASC) have the highest net survival and when accounting for other factors there are no differences amongst these morphological subtypes in terms of survival.